Efficacy of Heat Mitigation Strategies on Core Temperature and Endurance Exercise: A Meta-Analysis - Alhadad, Sharifah Badriyah; Tan, Pearl M. S.; Lee, Jason K. W. (Frontiers in Physiology, 2019)
A majority of high profile international sporting events, including the coming 2020 Tokyo Olympics, are held in warm and humid conditions. When exercising in the heat, the rapid rise of body core temperature (Tc) often results in an impairment of exercise capacity and performance. As such, heat mitigation strategies such as aerobic fitness (AF), heat acclimation/acclimatization (HA), pre-exercise cooling (PC) and fluid ingestion (FI) can be introduced to counteract the debilitating effects of heat strain. We performed a meta-analysis to evaluate the effectiveness of these mitigation strategies using magnitude-based interferences. A computer-based literature search was performed up to 24 July 2018 using the electronic databases: PubMed, SPORTDiscus and Google Scholar. After applying a set of inclusion and exclusion criteria, a total of 118 studies were selected for evaluation. Each study was assessed according to the intervention’s ability to lower Tc before exercise, attenuate the rise of Tc during exercise, extend Tc at the end of exercise and improve endurance. Weighted averages of Hedges’ g were calculated for each strategy. PC (g=1.01) was most effective in lowering Tc before exercise, followed by HA (g=0.72), AF (g=0.65) and FI (g=0.11). FI (g=0.70) was most effective in attenuating the rate of rise of Tc, followed by HA (g=0.35), AF (g=-0.03) and PC (g=-0.46). In extending Tc at the end of exercise, AF (g=1.11) was most influential, followed by HA (g=-0.28), PC (g=-0.29) and FI (g=-0.50). In combination, AF (g=0.45) was most effective at favourably altering Tc, followed by HA (g=0.42), PC (g=0.11) and FI (g=0.09). AF (1.01) was also found to be most effective in improving endurance, followed by HA (0.19), FI (-0.16) and PC (-0.20). AF was found to be the most effective in terms of a strategy’s ability to favourably alter Tc, followed by HA, PC and lastly, FI. Interestingly, a similar ranking was observed in improving endurance, with AF being the most effective, followed by HA, FI and PC. Knowledge gained from this meta-analysis will be useful in allowing athletes, coaches and sport scientists to make informed decisions when employing heat mitigation strategies during competitions in hot environments.